PENERAPAN MODEL COOPERATIVE LEARNING TIPE STUDENT TEAMS ACHIEVEMENT DIVISION (STAD) DALAM PEMBELAJARAN MENULIS TEKS ULASAN PADA PESERTA DIDIK KELAS VIII SMP PUI GEGESIK KABUPATEN CIREBON - Siti Nurokhmah; Ade Hasanudin; Fithry Muthmainnah (Program Studi Pendidikan Guru Sekolah Dasar FKIP Universitas Pasundan, 2025)
This research aims to determine the effectiveness of the Student Teams Achievement Division (STAD) type cooperative learning model in learning to write review texts for class VIII students at PUI Gegesik Middle School. This research is a type of quasi experiment. The design used was nonequivalent control group design, with the sample consisting of two classes, namely class VIII A with a total of 24 and class VIII B with a total of 24. The sampling technique used was purposive sampling. Based on the data, it shows that the final average score for the experimental class learning outcomes using the STAD learning model is 78.1, while the final average score for the control class learning outcomes using the expository learning model is 67.5. Obtained a calculated t value of 5.526, the t table value refers to the formula (a/2); (df) equals (0.05/2); (46) equals 0.025; 46. ​​In this value, in the statistical table t value distribution, the t table value was found to be 2.014. Thus the calculated t value is 5.526 > t table 2.014, so that in this test it shows that the alternative hypothesis (Ha) which states